2016
DOI: 10.1177/0044118x14531604
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Mentoring Relationship Quality Scale

Abstract: Youth mentoring relationships have significant potential for promoting positive youth development. Nonetheless, the benefits derived from such relationships depend considerably on the length and quality of the bonds that are created between mentors and youth. Although some attention has been paid to youth's experience of relationship quality, few studies have focused on mentors' experience of relationship quality. In the context of a national sample of mentor and youth dyads in Big Brothers Big Sisters communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 40 publications
(71 reference statements)
0
45
1
14
Order By: Relevance
“…Despite the lower reports on the strength of the mentoring relationship among mentors with VI, the smaller number of match meetings, and the shorter the durations of these meetings, mentees with VI felt their relationships were just as strong as relationships involving sighted mentors. This finding is not consistent with recent research that showed that a higher frequency of match meetings and longer lengths of match duration are associated with higher relationship quality (Eby et al., ; Herrera et al., ; Rhodes et al., ). Perhaps practical limitations, such as restrictions in mobility, orientation, and fatigue, limit the ability of mentors with VI to meet more frequently and arrange meetings of longer duration with their mentees.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Despite the lower reports on the strength of the mentoring relationship among mentors with VI, the smaller number of match meetings, and the shorter the durations of these meetings, mentees with VI felt their relationships were just as strong as relationships involving sighted mentors. This finding is not consistent with recent research that showed that a higher frequency of match meetings and longer lengths of match duration are associated with higher relationship quality (Eby et al., ; Herrera et al., ; Rhodes et al., ). Perhaps practical limitations, such as restrictions in mobility, orientation, and fatigue, limit the ability of mentors with VI to meet more frequently and arrange meetings of longer duration with their mentees.…”
Section: Discussioncontrasting
confidence: 91%
“…Strength of the relationship . We used a translated version of the 10‐item Youth Strength of Relationship Scale (Rhodes et al., ; e.g., “When I am with my mentor, I feel safe”) to assess mentee's perceptions of the strength of their mentoring relationships. Participants rated the answers on a 5‐point Likert scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A closer inspection of the data revealed that youth provided the highest ratings followed by parents. Elevated levels of MRQ among youth relative to mentor reports have been reported in other work (e.g., Goldner & Mayseless, 2009;Rhodes, Schwartz, Willis, & Wu, 2017). Mentored youth may harbor unrealistic expectations of an immediate deepening of the mentoring relationship or an intense desire to see it succeed (Goldner & Mayseless, 2009) and therefore may be willing to downplay negative experiences while attributing positive qualities to their mentors.…”
Section: Discussionmentioning
confidence: 76%
“…In line with these perspectives, youth perceptions of the quality of their relationships with mentors assigned to them through programs such as Big Brothers Big Sisters (BBBS) have been identified as a significant correlate of reduced aggression in high risk mentored youth (Cavell, Elledge, Malcolm, Faith, & Hughes, 2009), more effective coping strategies (Chesmore, Weiler, & Taussig, 2017), improved social skills (e.g., cooperation, self-control, assertiveness, empathy; Sale, Bellamy, Springer, & Wang, 2008), higher levels of scholastic competence, school bonding, and educational aspirations (Goldner & Mayseless, 2009;Liao & Sanchez, 2016;Rhodes, Reddy, Roffman, & Grossman, 2005;Zand et al, 2009), and improved interpersonal relationships with family and peers (Goldner & Mayseless, 2009;Thomson & Zand, 2010). In addition, high MRQ as reported by youth is correlated with widely acknowledged benchmarks for achieving program success such as longer and more stable mentoring relationships (often referred to as "matches") and matches with greater frequency and intensity of monthly contact (De Wit, DuBois, Erdem, Larose, Lipman, & Spencer, 2016;Rhodes, Schwartz, Willis, & Wu, 2017). Despite this evidence in support of a critical role for MRQ in mediating the benefits of youths' participation in mentoring programs, little is known of the underlying factors that contribute to their formation.…”
mentioning
confidence: 99%